2020
DOI: 10.1007/s11695-020-04582-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Vitamin D Status and PTH over 5 Years After Roux-en-Y Gastric Bypass: a Longitudinal Cohort Study

Abstract: Purpose Secondary hyperparathyroidism (SHPT) after obesity surgery may affect bone health. Optimal vitamin D levels have not been established to prevent SHPT postoperatively. We investigated whether SHPT differed across threshold levels of serum 25-hydroxyvitamin D (S-25(OH)D) from 6 months up to 5 years after Roux-en-Y gastric bypass (RYGB). Materials and Methods We included 554 patients at follow-up 5 years postoperatively. Blood samples were analysed for S-25(OH)D, ionized calcium (iCa) and parathyroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…After the exclusion of ineligible studies, our final sample was 30 studies. 4,5,[7][8][9][10][11][14][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Among them, four studies had two arms, these arms were analyzed separately in this meta-analysis 14,31,34,39 (Figure 1). The characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of ineligible studies, our final sample was 30 studies. 4,5,[7][8][9][10][11][14][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Among them, four studies had two arms, these arms were analyzed separately in this meta-analysis 14,31,34,39 (Figure 1). The characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The study quality assessment is also displayed in this table. Of all included studies, 30 were considered inadequate for vitamin D and calcium supplementation, [7][8][9][10]14,16,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 4 were assessed as adequate supplementation 4,5,11,15 (Table 2). Of the 30 studies with inadequate supplementation, 6 reported data for ≤1 year of follow-up, 19 for >1 and ≤5 years, 3 for >5 and ≤10 years, and 2 for >10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, calcium is absorbed passively as well as actively in the small intestine, and a study using a dual stable calcium isotope method ( 198 ) demonstrated a significant reduction in calcium absorption following RYGB despite adequate vitamin D and calcium intake. With concern to vitamin D, even solely restrictive procedures like SG can lead to postoperative vitamin D deficiency in as much as 39% of patients despite daily multivitamin supplementation ( 199 ), while malabsorptive surgeries pose a higher risk for nutrient deficiencies ( 200 ). In a retrospective study, a 73% incidence of vitamin D deficiency was observed following BPD ( 201 ).…”
Section: Potential Mechanisms Associated With Bone Loss After Bariatr...mentioning
confidence: 99%
“…despite adequate vitamin D and calcium intake. With concern to vitamin D, even solely restrictive procedures like SG can lead to postoperative vitamin D deficiency in as much as 39% of patients despite daily multivitamin supplementation (199), while malabsorptive surgeries pose a higher risk for nutrient deficiencies (200). In a retrospective study, a 73% incidence of vitamin D deficiency was observed following BPD (201).…”
Section: Alterations In Bonementioning
confidence: 99%
“…As the risk of cholelithiasis increases after metabolic surgery [ 219 ], regularly examination by abdominal ultrasonography would be preferred. Furthermore, since bone mass may reduce due to secondary hyperparathyroidism associated with vitamin D and calcium deficiency after metabolic surgery [ 220 , 221 ], bone mineral density evaluation would be preferred every 2 years.…”
Section: Preoperative Managementmentioning
confidence: 99%